Medpredmetno povezovanje gibanja in glasbe v zgodnjem obdobju otroštva - Marinšek, Miha; Šumer, Manja; Denac, Olga (Revija za elementarno izobraževanje, 2020)
Integration of Movement and Music in Early Childhood. The purpose of this study was to examine the influence of an experimental programme based on the integration of movement and music on the development of fundamental movement skills and rhythmic abilities. Sixtytwo children aged from 5 to 6 years participated in the study. Results showed that children who were included in the music and movement  programme as well as those included in the movement-only programme improved more in fundamental movement skills and rhythmic abilities than children from the control group. Considering the principle of horizontal integration of different curricular areas and different viewpoints on the child’s development andlearning, the experimental music and movement programme proved to be more effective.
Keywords: movement skills; rhythmic abilities; principle of integration; integration of movement and music; experimental programme